THE ROLE OF FINANCIAL INFORMATION SYSTEMS IN FINANCIAL PERFORMANCE - Jasim, Layla; Gatea, Ali khalaf (Socio-economic relations in the digital society, 2025)
This study aims to demonstrate how financial information systems improve the financial performance of banks and financial institutions in Iraq by analyzing revenue increases, cost reductions, and financial transparency. Financial information systems play a pivotal role in improving the financial performance of institutions by providing accurate and reliable data that supports the decision-making process. The study attempts to clarify how institutions invest in financial information systems to achieve their financial goals and enhance their competitiveness. It also seeks to determine how these methods are applied and the extent to which they improve financial performance. The basic hypothesis of the study is that current financial information systems improve institutions' financial performance, enhance operational efficiency, reduce financial errors, and provide accurate data quickly. The research also indicates that institutions that invest in advanced financial information systems will be better able to expand financially and adapt to rapid economic changes than those that use traditional or inefficient systems. The results of the statistical analysis showed a statistically significant correlation and impact of financial information systems on the financial performance of the banks under study. Among the study's most important conclusions is that the speed, timeliness, importance, originality, sophistication, and operational efficiency of the financial information system had a statistically significant impact on the financial performance of banks.
Keywords: financial information systems; financial performance; banks; transparency